Cover Picture: Point‐of‐care detection of cytokines in cytokine storm management and beyond: Significance and challenges (View 4/2021). Issue 4 (29th August 2021) - Liu, Guozhen; Jiang, Cheng; Lin, Xiaoting; Yang, Yang
Abstract : In article number 20210003, Guozhen Liu, Cheng Jiang and their co‐workers demonstrates that cytokines are signalling molecules between cells in immune system, and are indicators of our body conditions. Cytokine storm can result in disease severity and major‐organ damage. Point‐of‐Care (POCT) testing will provide clinical significance in disease early‐diagnosis and management. With the aid of nanobiotechnology, engineering and artificial intelligence, integrated portable devices are able to provide rapid and sensitive quantification of cytokines in real‐time in clinical samples towards next‐generation healthcare monitoring and management. Cytokine POCT is expected to be the key player under the spotlight of disease management and prevention during COVID‐19 pandemic and also the post COVID‐19 pandemic era.